Visual forms of carved components in traditional timber houses of Kelantan and Terengganu - Kamarudin, Zumahiran; Said, Ismail (2008)
Malay traditional timber houses of Kelantan and Terengganu are normally adorned with decorative carved components which represent excellent carvings in its specified design motif, shape, size and layout. Various carved components with specific features are fabricated according to its placement and configuration in the interior as well as exterior setting of the houses. Woodcarving as an embellishment is a significant unifying architectural element between the house forms and its building components. This paper presents an explorative study of the visual forms and placement of carved components in the vernacular houses of Kelantan and Terengganu which denotes its significant attributes and uses. A set of 13 case studies, nine houses in Kelantan and four houses in Terengganu were referred to as the research base. The methods of investigation include analytical review of measured drawings and reports of the Kelantan and Terengganu timber houses from the Centre for the Study of Built Environment in the Malay World (KALAM) at the Department of Architecture in the Universiti Teknologi Malaysia (UTM) and narrations from the prominent woodcarvers on art and crafts of woodcarving. Apart from these methods, interviews with the allied professionals for scholastic information on art and architecture of the Malay world were also conducted. The analysis of the documents revealed that several types of carved components with distinctive visual forms in two and three dimensional composition were placed in certain orders within the fabrics of the houses. Wall, door and window ventilation panels, railings, gate panel and stringers are types of components characterized by the shape of perforation and incision with relief and/or non-relief carvings. These components were crafted in relation to the house form and architectural elements such as wall, door, window, stair and gate. The significant aspect of the placement of the carvings in the houses is that it enhances beautiful ambiance and signifies regional identity to the vernacular architecture of these two states.